Atomically dispersed Cu coordinated Rh metallene arrays for simultaneously electrochemical aniline synthesis and biomass upgrading - Mao, Qiqi; Mu, Xu; Wang, Wenxin; Deng, Kai; Yu, Hongjie; Wang, Ziqiang; Xu, You; Wang, Liang; Wang, Hongjing (Nature communications, 2023)
Organic electrocatalytic conversion is an essential pathway for the green conversion of low-cost organic compounds to high-value chemicals, which urgently demands the development of efficient electrocatalysts. Here, we report a Cu single-atom dispersed Rh metallene arrays on Cu foam for cathodic nitrobenzene electroreduction reaction and anodic methanol oxidation reaction. In the coupled electrocatalytic system, the Cu single-atom -Rh metallene arrays on Cu foam requires only the low voltages of 1.18 V to reach current densities of 100 mA cm −2 for generating aniline and formate, with up to ~100% of nitrobenzene conversion/ aniline selectivity and over ~90% of formate Faraday efficiency, achieving synthesis of high-value chemicals. Density functional theory calculations reveal the electron effect between Cu single-atom and Rh host and catalytic reaction mechanism. The synergistic catalytic effect and H*-spillover effect can improve catalytic reaction process and reduce energy barrier for reaction process, thus enhancing electrocatalytic reaction activity and target product selectivity. Electrocatalytic conversion of low-cost organic compounds to high-value chemicals urgently demands the development of efficient electrocatalysts. Mao et al. report the synthesis of Cu single-atom dispersed Rh metallene arrays for electrochemical aniline synthesis and biomass upgrading with enhanced electrocatalytic activity.